Next-Generation Payment Protocols: Architecting Secure, Scalable, and Real-Time Transaction Systems - Shatrughna Upadhyay, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
The evolution of digital payment systems represents a critical transformation in global financial infrastructure, driven by increasing demands for faster, more secure, and scalable transaction processing. This comprehensive article examines the architecture, implementation, and future directions of next-generation payment protocols, focusing on three fundamental pillars: ISO 20022 messaging standards, Layer 2 scaling solutions, and real-time settlement networks. The article analyzes how these components work in concert to address current limitations in traditional payment systems while enabling new capabilities in cross-border transactions, micro-payments, and real-time settlement. Through examination of major implementations including RTP, FPS, and UPI, the article reveals key success factors in deploying modern payment infrastructure. The article encompasses performance optimization strategies, scalability approaches, and security considerations, providing insights into best practices for financial institutions undertaking payment system modernization. The article demonstrates how emerging technologies, including artificial intelligence, edge computing, and quantum-resistant cryptography, are shaping the future of payment protocols while addressing critical challenges in global financial operations.
Keywords: Payment Protocols; Real-time Settlement; ISO 20022; Financial Technology; Transaction Security